Automated overtaking assistance system: a real-time approach using deep learning techniques - Moonjarin, Musarrat; Charu, Krity Haque; Nafis, Kh. Fardin Zubair; Sawly, Suraya Jahan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.